Pillar[n]arene-based porous polymers for rapid pollutant removal from water. Issue 6 (30th January 2017) - Lan, Shang; Zhan, Shuaijun; Ding, Jiaming; Ma, Jiaqi; Ma, Da
Abstract : Pillararene-based polymers are superior adsorbents for paraquat. Abstract : Pillar[ n ]arene (PA[ n ], n = 5 or 6) based porous polymers (P-PAP[ n ]s) were prepared by crosslinking PA[ n ]s and used as adsorbents to remove pollutants from water via host–guest interactions. These new materials are adsorbents for a wide range of contaminants with fast removal kinetics. The adsorption is especially efficient for herbicide paraquat with very fast uptake kinetics ( k 2 = 33.3 g mg −1 min −1, at least 5 times faster than that of any existing adsorbent for paraquat) and a high removal capacity (209 mg g −1 ).